Development, Optimization and Validation of RF-HPLC-FL Method for Simultaneous Determination of Aflatoxins, Ochratoxin A and Zearalenone in Cereals - Rahmani, Anosheh (2010)
The heightened awareness of consumer-health risk from cumulative mycotoxin exposure has resulted in the establishment of regulatory limits that can protect human risk from the consumption of food products containing mycotoxin. Consequently, cost-effective, time saving, trace level simultaneous detection methods for controlling main mycotoxins in foods became highly desired. This research has been conducted to develop a reverse phase high performance liquid chromatography fluorescence detection (RP-HPLC-FLD) method for simultaneous determination of six mycotoxins (aflatoxin B1, B2, G1 and G2, ochratoxin A and zearalenone) in cereals. It has been found that injecting 100μL of mycotoxin standard to a symmetry C18 column in appropriate combination of methanol: acetonitrile: phosphoric acid (1%) (30:10:60 (v/v) for 0-14 min and 10:45:45 (v/v) for 12-35min in suitable excitation and emission wavelengths of fluorescent detector can grant separation of six mycotoxins in 35 minutes. Then, the developed method was optimized using an experimental design including fractional factorial design (FFD)followed by response surface methodology (RSM). In this study, the effect of seven variables including temperature (20-40oC), flow rate (0.8-1.2 ml/min), acid concentration in aqueous phase (0-2%), organic solvent percentage at start (40-50%) and end (50-60%) of the gradient mobile phase, ratio of methanol/acetonitrile at start (1-4) and end (0-1) of gradient mobile phase, have been evaluated on HPLC responses (separation and resolutions of peaks and HPLC run time). The statistical optimized HPLC condition for response variables (separation and resolutions of peaks and HPLC run time) was validated statistically and experimentally. The optimal conditions was 41% and 60% organic solvent percentage at start and end of gradient mobile phase, 1.93 and 0.2 methanol/acetonitrile ratio at start and end of gradient respectively, 0.1% acid concentration in aqueous phase, at 1 ml/min flow rate and in 40oC column oven temperature. After that, the efficiency of three extraction solvents including methanol: water (80:20 v/v), acetonitrile: water (80:20 v/v) and acetonitrile: water (60:40 v/v) and three clean-up procedures including multi-functional AOZ immunoaffinity column (IAC), OASIS HLB solid phase extraction column and multi- functional MycoSep column were compared using spiked rice sample. The highest recovery of mycotoxins (93-104%) was obtained by using methanol: water (80:20 v/v) as extraction solvent and IAC as clean-up method. Application of optimized simultaneous determination method on spiked cereal samples (rice, barley, oat, wheat and corn) showed 74-104 % recovery for all six mycotoxins and acceptable precision in all cereals. The optimized HPLC- FLD method was validated through determination of selectivity, sensitivity, linearity and precision. Limit of detection (LOD) and quantification (LOQ) of these mycotoxins ranged 0.004 - 0.5ng/g and 0.015 -2 ng/g, respectively. To confirm the performance of HPLC method for simultaneous determination of mycotoxins on real cereal samples a total of 61 samples of cereals (including rice, oat, barley, wheat and maize) were randomly collected from food stores in Selangor State, Malaysia and were analyzed for mycotoxins using the HPLC simultaneous determination method. The results showed low occurrence of these mycotoxins in commercial cereals marketed in Malaysia. In conclusion, the newly developed, optimized and validated HPLC-FLD method is an efficient and accurate method for simultaneous determination of these mycotoxins and could be used for routine analysis in the mycotoxin laboratories.